A kind of water-based low-temperature paint and preparation method thereof

By using specific ratios of hydrophobic nano silica microcapsules with hydrophobic loaded polyammonium phosphate and concave and concave rod soil in aqueous low-temperature color paint, combined with raw materials such as aqueous acrylic emulsion, the performance of aqueous color paint under low-temperature curing conditions is solved. The problems of instability, insufficient water resistance and flame retardancy have achieved high-performance water-based low-temperature paint, supporting the green transformation of the automotive industry.

CN118685084BActive Publication Date: 2024-12-17HUIZHOU JUXIN CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410894005.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2024-12-17
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The existing water-based colored paint has unstable performance under low temperature curing conditions, and its water resistance and flame retardancy are poor, which limits its wide application in the automotive coating industry and affects the green transformation process of the automotive industry.

Method used

Using the specific ratio of nano-silica microcapsules with hydrophobic loaded polyammonium phosphate and concave and concave rod soil, combined with water-based acrylic emulsion, titanium dioxide and other raw materials, it forms highly waterproof and flame retardant through carefully designed formulas and preparation methods. Performance water-based low-temperature paint.

Benefits of technology

It significantly improves the waterproof, flame retardant and mechanical properties of the coating, meets the environmental protection requirements of the automotive coating industry, extends the service life of the coating, and promotes the automobile manufacturing industry toward green and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004928403390000141
    Figure BDA0004928403390000141
  • Figure BDA0004928403390000142
    Figure BDA0004928403390000142
  • Figure BDA0004928403390000151
    Figure BDA0004928403390000151
Patent Text Reader

Abstract

The present application discloses a water-based low-temperature paint and a preparation method thereof, wherein the water-based low-temperature paint comprises the following raw materials by weight: 5575 parts of water-based acrylic emulsion; 24 parts of amine neutralizer; 13 parts of defoamer; 30-35 parts of titanium dioxide; 12 parts of sodium dodecylbenzene sulfonate; 11.5 parts of leveling agent; 46 parts of polypropylene glycol; 1825 parts of deionized water; 69 parts of ethanol; 410 parts of diethylene glycol butyl ether; 58 parts of propylene glycol butyl ether; 13 parts of thickener; 35 parts of light stabilizer; 5-9 parts of water-based silane coupling agent; 10-20 parts of hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate; 5-10 parts of attapulgite. The water-based low-temperature paint provided by the present application has the advantages of good water resistance and flame retardancy, and can be quickly cured under low temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating technology, and in particular to a water-based low-temperature paint and a preparation method thereof. Background Art

[0002] The solvent-based automotive coatings currently widely used in my country's automotive manufacturing industry contain a high proportion of harmful organic solvents, which will produce a large amount of VOCs during the production and spraying process, posing a significant threat to air quality, operator safety and the ecological environment. In response to this major environmental protection issue, the coatings technology community has long been committed to developing low-VOC or even zero-VOC alternatives. Although significant breakthroughs have been made in scientific research, such as the successful development and widespread application of water-based primers, mid-coats and metallic paints, which have greatly reduced the use and emissions of organic solvents, the technical difficulties of the last link in the automotive coating process - water-based color paints and clear varnishes - have not been completely solved, which has prevented the environmental protection transformation of the entire automotive spraying process from coming to a successful conclusion. At the same time, the poor water resistance and flame retardancy of current water-based color paints also restrict their promotion and application under a wider range of conditions, which in turn affects the green transformation process of the entire automotive industry. Summary of the invention

[0003] In order to solve at least one of the above technical problems, a water-based low-temperature paint with good environmental protection, waterproofness and flame retardancy is developed. The present application provides a water-based low-temperature paint and a preparation method thereof.

[0004] In a first aspect, the present application provides a water-based low-temperature paint, which comprises the following raw materials in parts by weight:

[0005] 5575 parts of water-based acrylic emulsion;

[0006] 24 parts of amine neutralizer;

[0007] 13 parts of defoaming agent;

[0008] 30-35 parts of titanium dioxide;

[0009] Sodium dodecylbenzenesulfonate 12 parts;

[0010] 11.5 parts of leveling agent;

[0011] 46 parts of polypropylene glycol;

[0012] 1825 parts of deionized water;

[0013] Ethanol 69 parts;

[0014] 410 parts of diethylene glycol butyl ether;

[0015] Propylene glycol butyl ether 58 parts;

[0016] Thickener 13 parts;

[0017] 35 parts of light stabilizer;

[0018] 5-9 parts of water-based silane coupling agent;

[0019] 10-20 parts of hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate;

[0020] 5-10 parts of attapulgite.

[0021] By adopting the above technical scheme, the water-based low-temperature paint formula provided by this application combines a variety of functional raw materials, aiming to achieve comprehensive improvement in environmental protection, waterproof and flame retardant properties. Among them, water-based acrylic emulsion as the main film-forming substance not only reduces the VOC content, but also ensures good adhesion and mechanical properties of the coating; amine neutralizer ensures that the emulsion is in a suitable pH range and remains stable; defoamer effectively removes foam during the mixing process; titanium dioxide provides good hiding power and lasting color; sodium dodecylbenzene sulfonate is used as a surfactant to improve dispersibility; leveling agent ensures the flatness of the paint film; polypropylene glycol enhances the flexibility and water resistance of the paint film; ethanol, diethylene glycol butyl ether and propylene glycol butyl ether are used as solvents, which not only adjust the viscosity of the coating, but also improve the construction performance at low temperatures, so that the coating can still be smoothly applied and quickly dried at lower temperatures. Deionized water is used as a diluent to maintain the water-based environmental protection characteristics of the system. The thickener controls the construction performance of the coating; the light stabilizer prevents ultraviolet aging; the water-based silane coupling agent strengthens the bonding between the paint film and the substrate, and further enhances the water resistance of the paint film; the hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate play a key role in the water-based low-temperature paint of this application. This innovative structural design allows the flame retardant to be evenly dispersed inside the coating to form a microscopic flame-retardant protective layer. When the coating encounters high temperatures, the microcapsules can quickly rupture and release ammonium polyphosphate, exerting a highly efficient flame retardant effect and enhancing the fire resistance of the coating. At the same time, the nano-silica itself has excellent density, which can improve the overall protective effectiveness of the coating, reduce water penetration, and further enhance the water resistance and durability of the coating.

[0022] On the other hand, the attapulgite added to the formula is a natural mineral with a special layered structure and strong adsorption capacity. After adding attapulgite to water-based paint, it can enhance the density of the coating and improve its ability to resist water penetration, thereby greatly improving the waterproof performance of the coating. At the same time, attapulgite can also enhance the bonding force between the coating and the substrate, increasing the mechanical strength and stability of the coating.

[0023] In general, the water-based low-temperature paint technology solution provided in this application integrates a variety of high-performance raw materials. By carefully adjusting the proportions and interactions of each component, it not only overcomes the problem of unstable performance of existing water-based paints under low-temperature curing conditions, but also focuses on solving the three key technical problems of environmental protection, waterproofness and flame retardancy of the coating. It achieves the goal of meeting the environmental protection requirements of the automotive coating industry while significantly improving the functionality and durability of the coating, which is of great significance for promoting the green and sustainable development of the automotive manufacturing industry.

[0024] Optionally, the weight ratio of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules to the attapulgite is (1.8-2.3):1.

[0025] By adopting the above technical scheme, the present application can accurately control the ratio of hydrophobic ammonium polyphosphate loaded nano-silica microcapsules and attapulgite in water-based low-temperature paint, which is set to a weight ratio of (1.8-2.3): 1. This specific ratio combination can achieve the following effects: the ammonium polyphosphate high-efficiency flame retardant in the microcapsule can be evenly distributed in the coating to form a microscopic flame retardant structure. When the coating is heated, the microcapsule quickly breaks and releases the flame retardant, greatly improving the fire resistance of the coating; the high density of nano-silica itself helps to enhance the overall protective effectiveness of the coating, reduce the water permeability, and further optimize the water resistance and durability of the coating; attapulgite, with its special layered structure and adsorption, effectively enhances the density of the coating and greatly improves the waterproof performance of the coating; at the same time, attapulgite can also enhance the bonding force between the coating and the substrate, and increase the mechanical strength and stability of the coating. Through such a proportion configuration, the present application not only solves the performance defects that may exist in water-based paint under low-temperature curing conditions, but also specially optimizes the environmental protection, waterproof and flame retardant properties of the coating, so that while meeting the strict environmental protection requirements of the automotive coating industry, the comprehensive quality and durability of water-based low-temperature paint are greatly improved, which has important practical significance and application value for promoting the green and sustainable development of the automotive manufacturing industry.

[0026] Optionally, the weight ratio of the nano-silica microcapsules loaded with ammonium polyphosphate to the attapulgite is 2.0:1.

[0027] By adopting the above technical scheme, the present application can achieve precise ratio control of nano-silica microcapsules loaded with ammonium polyphosphate and attapulgite in water-based low-temperature paint, setting it to a weight ratio of 2.0:1. This specific ratio design brings the following advantages: by incorporating nano-silica microcapsules loaded with ammonium polyphosphate into the paint in an appropriate proportion, a uniformly dispersed flame retardant network can be constructed inside the coating. When the coating is exposed to a high temperature environment, the microcapsules can quickly rupture and release ammonium polyphosphate, thereby exerting an efficient flame retardant effect and greatly improving the fire resistance of the coating. The self-density characteristics of nano-silica microcapsules help to enhance the overall protective performance of the coating, reduce water infiltration, and thus significantly enhance the water resistance and durability of the coating. As a special filler, attapulgite, with its unique layered structure and strong adsorption properties, can not only further improve the density of the coating and significantly enhance the waterproof performance of the coating, but also enhance the bonding force between the coating and the underlying material, effectively improving the mechanical strength and stability of the coating. By selecting the specific ratio of 2.0:1 to mix the nano-silica microcapsules loaded with ammonium polyphosphate and attapulgite, the present application effectively solves the key technical problems of water-based low-temperature paint in terms of environmental protection, waterproofness and flame retardancy, thereby greatly improving the product quality and service life of the paint while ensuring the low-temperature curing performance. This has a positive role in promoting the development of the automotive manufacturing industry towards a more environmentally friendly, safe and sustainable direction.

[0028] Optionally, the total weight of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and the attapulgite accounts for 12.50-15.15% of the total weight of the water-based low-temperature paint.

[0029] By adopting the above technical solution, the present application controls the total weight of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite within the range of 12.50-15.15% of the total weight of the water-based low-temperature paint, and the present application can achieve the following key advantages: This ratio range can ensure that the coating has excellent flame retardancy and waterproof properties while avoiding excessive use of ingredients and maintaining the best balance of cost-effectiveness. This is crucial for large-scale production and commercial applications, which can not only ensure product quality but also control production costs. This ratio ensures the effective distribution and effect of flame retardants and reinforcing materials. The hydrophobic properties and intelligent release mechanism of nano-silica microcapsules, combined with the strong adsorption capacity and structural enhancement effect of attapulgite, not only improve the fireproof level of the coating, but also enhance the physical strength and durability of the coating, effectively prevent moisture penetration, and extend the service life of the coating. While ensuring high performance, this ratio setting also fully considers environmental protection requirements. The selection and proportioning of all ingredients are aimed at reducing the impact on the environment, supporting the development of the automotive manufacturing industry in a green and sustainable direction, and conforming to international environmental protection trends and consumers' expectations for environmentally friendly products. In summary, by carefully designing the ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite in water-based low-temperature paint, this application not only achieves a key performance breakthrough in coating technology, but also demonstrates significant advantages in cost control, environmental adaptability, and sustainable development, providing advanced solutions for the automotive coating industry and other related fields.

[0030] Optionally, the preparation method of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules is as follows:

[0031] A1, sorbitan oleate and octylphenol polyoxyethylene ether-10 were mixed, and cyclohexane and ammonia water were added, and the mixture was stirred to obtain an oil phase;

[0032] A2, mixing ammonium polyphosphate and water in a weight ratio of (8-10):100, and dispersing and dissolving by ultrasonication to obtain an aqueous phase;

[0033] A3, under stirring, the water phase is added dropwise to the oil phase for 45-60 minutes, followed by emulsification for 30-45 minutes to form a water-in-oil emulsion, and finally, ethyl orthosilicate is added dropwise for 45-60 minutes, followed by reaction for 24 hours to obtain an emulsion;

[0034] A4, demulsifying the emulsion with anhydrous ethanol, centrifuging for 3 times, and drying in an oven at 50° C. for 22-24 hours to obtain non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules;

[0035] A5, mixing hexadecyltrimethoxysilane and anhydrous ethanol solution, and adding the non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules obtained in step A4, stirring at 60-70° C. for 5-6 hours, and centrifuging and washing to obtain the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules;

[0036] In the step A1, the weight ratio of sorbitan oleate, octylphenol polyoxyethylene ether-10, cyclohexane and ammonia water is 8:1:(90-100):(3-5);

[0037] The weight ratio of the ammonium polyphosphate in step A2 to the sorbitan oleate in step A1 is (1.5-2):8;

[0038] In the step A3, the weight ratio of the tetraethyl orthosilicate to the sorbitan oleate is 30:(8-10);

[0039] In the step A4, the weight ratio of the emulsion to the anhydrous ethanol is 2:1;

[0040] In the step A5, the weight ratio of the hexadecyltrimethoxysilane to the sorbitan oleate is (5-6):8;

[0041] In step A5, the weight ratio of the hexadecyltrimethoxysilane to the anhydrous ethanol solution is (6-8):100.

[0042] By adopting the above technical scheme, the present application aims to successfully prepare nano-silica microcapsules loaded with ammonium polyphosphate with excellent hydrophobic properties through a well-designed multi-step chemical reaction process through the preparation method of the above-mentioned hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules. First, a surfactant and a solvent are mixed in a specific proportion to form a stable oil phase environment; then, the ammonium polyphosphate is dissolved in the aqueous phase and the condensation reaction of ethyl orthosilicate in water is used to generate silica nano-microspheres in an inverse system, and this microsphere structure effectively loads the ammonium polyphosphate. This load structure is subsequently solidified through emulsification, demulsification and drying steps to form a preliminary microcapsule. Finally, the preliminarily prepared microcapsules are hydrophobically modified by hexadecyltrimethoxysilane and anhydrous ethanol solution to enhance the hydrophobicity of the microcapsule surface, ensure that the internally loaded ammonium polyphosphate can be stably present in various environments, and may be slowly released when needed, while maintaining good water resistance and stability. This method not only ensures the integrity of the microcapsule structure, but also significantly enhances its functional application potential, such as in flame retardancy and sustained release.

[0043] Optionally, the defoaming agent is selected from silicone oil defoaming agents.

[0044] Optionally, the leveling agent is selected from diacetone alcohol.

[0045] Optionally, the thickener is selected from associative polyurethane thickeners.

[0046] Optionally, the light stabilizer is selected from benzotriazole light stabilizers.

[0047] In a second aspect, the present application provides a method for preparing a water-based low-temperature paint, the preparation method comprising the following steps: S1, mixing deionized water, sodium dodecylbenzene sulfonate, hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules, and attapulgite to prepare a first mixture;

[0048] S2, mixing diethylene glycol butyl ether, propylene glycol butyl ether and the first mixed material, and then adding titanium dioxide to obtain a second mixed material;

[0049] S3, adding the water-based acrylic emulsion and the amine neutralizer to the second mixture, and then adding the light stabilizer and the water-based silane coupling agent, mixing and stirring to obtain a third mixture;

[0050] S4. Add the remaining ingredients to the third mixture, stir and mix them evenly at a speed of 600-800 r / min for 5-10 minutes to obtain the water-based low-temperature paint.

[0051] By adopting the above technical scheme, the water-based low-temperature paint preparation method provided by the present application is a systematic and orderly synthesis process. First, in step S1, deionized water, surfactant sodium dodecylbenzene sulfonate, hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate with flame retardant and waterproof properties, and attapulgite for improving coating compactness and waterproofness are fully mixed to form a preliminary basic mixed material. Subsequently, in step S2, diethylene glycol butyl ether and propylene glycol butyl ether are added to the basic mixed material as solvents and cosolvents, and titanium dioxide is further added to complete the second mixed material of pigment dispersion. Next, in step S3, an aqueous acrylic emulsion is combined with an amine neutralizer to form a stable emulsion system, and on this basis, a light stabilizer is added to enhance the anti-aging performance of the paint, and an aqueous silane coupling agent is added to enhance the bonding force between the paint film and the substrate to form a third mixed material containing a core film-forming substance. Finally, in step S4, all the remaining ingredients are added to the third mixed material one by one, and stirred and mixed evenly at a speed of 600 to 800 rpm for 5 to 10 minutes to successfully prepare a water-based low-temperature paint that is environmentally friendly, low-temperature curing, and has good waterproof and flame retardant properties. This preparation method ensures that the water-based low-temperature paint has excellent application performance and environmental protection properties by finely controlling each step and component ratio.

[0052] In summary, the present invention includes at least one of the following beneficial technical effects:

[0053] 1. The water-based low-temperature paint formula provided in this application combines a variety of functional raw materials, aiming to achieve a comprehensive improvement in environmental protection, waterproof and flame retardant properties. Among them, the hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate play a key role in the water-based low-temperature paint of this application. The design of this innovative structure allows the flame retardant to be evenly dispersed inside the coating to form a microscopic flame retardant protective layer. When the coating encounters high temperature, the microcapsules can quickly break and release ammonium polyphosphate, play an efficient flame retardant role, and enhance the fire resistance of the coating. At the same time, nano-silica itself has excellent compactness, which can improve the overall protective effectiveness of the coating, reduce water penetration, and further enhance the water resistance and durability of the coating. On the other hand, the attapulgite added in the formula is a natural mineral with a special layered structure and strong adsorption capacity. After adding attapulgite to the water-based paint, the compactness of the coating can be enhanced, and its ability to resist water penetration can be improved, thereby greatly improving the waterproof performance of the coating. At the same time, attapulgite can also enhance the bonding force between the coating and the substrate, increasing the mechanical strength and stability of the coating. In general, the water-based low-temperature paint technology solution provided in this application integrates a variety of high-performance raw materials. By carefully adjusting the proportions and interactions of each component, it not only overcomes the problem of unstable performance of existing water-based paints under low-temperature curing conditions, but also focuses on solving the three key technical problems of environmental protection, waterproofness and flame retardancy of the coating. It achieves the goal of meeting the environmental protection requirements of the automotive coating industry while significantly improving the functionality and durability of the coating, which is of great significance for promoting the green and sustainable development of the automotive manufacturing industry.

[0054] 2. This application can accurately control the ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite in water-based low-temperature paint, and set it to a weight ratio of (1.8-2.3): 1. This specific ratio combination can achieve the following effects: the ammonium polyphosphate high-efficiency flame retardant in the microcapsules can be evenly distributed in the coating to form a microscopic flame retardant structure. When the coating is heated, the microcapsules quickly rupture and release the flame retardant, greatly improving the fire resistance of the coating; the high density of nano-silica itself helps to enhance the overall protective effectiveness of the coating, reduce the water permeability, and further optimize the water resistance and durability of the coating; attapulgite, with its special layered structure and adsorption, effectively enhances the density of the coating and greatly improves the waterproof performance of the coating; at the same time, attapulgite can also enhance the bonding force between the coating and the substrate, and increase the mechanical strength and stability of the coating. Through such a proportion configuration, the present application not only solves the performance defects that may exist in water-based paint under low-temperature curing conditions, but also specially optimizes the environmental protection, waterproof and flame retardant properties of the coating, so that while meeting the strict environmental protection requirements of the automotive coating industry, the comprehensive quality and durability of water-based low-temperature paint are greatly improved, which has important practical significance and application value for promoting the green and sustainable development of the automotive manufacturing industry.

[0055] 3. The present application aims to successfully prepare nano-silica microcapsules loaded with ammonium polyphosphate with excellent hydrophobic properties through a carefully designed multi-step chemical reaction process through the above-mentioned preparation method of hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate. First, a surfactant and a solvent are mixed in a specific proportion to form a stable oil phase environment; then, ammonium polyphosphate is dissolved in the aqueous phase and the condensation reaction of ethyl orthosilicate in water is used to generate silica nano-microspheres in an inverse system. This microsphere structure effectively loads ammonium polyphosphate. This load structure is subsequently solidified through steps such as emulsification, demulsification and drying to form a preliminary microcapsule. Finally, the preliminarily prepared microcapsules are hydrophobically modified by hexadecyltrimethoxysilane and anhydrous ethanol solution to enhance the hydrophobicity of the microcapsule surface, ensure that the internally loaded ammonium polyphosphate can be stably present in various environments, and may be slowly released when needed, while maintaining good water resistance and stability. This method not only ensures the integrity of the microcapsule structure, but also significantly improves its functional application potential, such as in the fields of flame retardancy and sustained release.

[0056] 4. The water-based low-temperature paint preparation method provided by the present application is a systematic and orderly synthesis process. First, in step S1, deionized water, surfactant sodium dodecylbenzene sulfonate, hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate with flame retardant and waterproof properties, and attapulgite that improves the compactness and waterproofness of the coating are fully mixed to form a preliminary basic mixed material. Subsequently, in step S2, diethylene glycol butyl ether and propylene glycol butyl ether are added to the basic mixed material as solvents and cosolvents, and titanium dioxide is further added to complete the second mixed material of pigment dispersion. Next, in step S3, an aqueous acrylic emulsion is combined with an amine neutralizer to form a stable emulsion system, and on this basis, a light stabilizer is added to enhance the anti-aging performance of the paint, and a water-based silane coupling agent is added to enhance the bonding force between the paint film and the substrate to form a third mixed material containing a core film-forming substance. Finally, in step S4, all the remaining ingredients are added to the third mixed material one by one, and stirred and mixed evenly at a speed of 600 to 800 rpm for 5 to 10 minutes to successfully prepare a water-based low-temperature paint that is environmentally friendly, low-temperature curing, and has good waterproof and flame retardant properties. This preparation method ensures that the water-based low-temperature paint has excellent application performance and environmental protection properties by finely controlling each step and component ratio. DETAILED DESCRIPTION

[0057] The present application is further described in detail below in conjunction with embodiments.

[0058] Water-based acrylic emulsion: Shandong Jilu Building Decoration Engineering Co., Ltd., item number 718A.

[0059] Amine neutralizer: Tianjin Ruike Chemical Trading Co., Ltd.

[0060] Silicone oil defoamer: Yantai Hengxin Chemical Technology Co., Ltd., the active ingredient content is 100%.

[0061] Diacetone alcohol: CAS number is 123-42-2, purity is 99%.

[0062] Associative polyurethane thickener: Wuxi Henderson Chemical Products Co., Ltd., the active ingredient content is 40%.

[0063] Benzotriazole light stabilizer: CAS number is 3896-11-5, purity is 99%.

[0064] Titanium dioxide: CAS number is 13463-67-7; purity is 99%.

[0065] Sodium dodecylbenzenesulfonate: CAS number is 25155-30-0, purity is 99%.

[0066] Polypropylene glycol: CAS number is 25322-69-4, Shanghai Yuanye Biotechnology Co., Ltd.

[0067] Ethanol: CAS number is 64-17-5, 95% ethanol.

[0068] Diethylene glycol butyl ether: CAS number 112-34-5, purity 99%.

[0069] Propylene glycol butyl ether: CAS No. 29387-86-8, purity 99%.

[0070] Water-based silane coupling agent: Water-based silane coupling agent KH560, purity 99%.

[0071] Ammonium polyphosphate: CAS No. 68333-79-9, purity 99%.

[0072] Nano silicon dioxide: CAS No. 7631-86-9, purity 99%.

[0073] Attapulgite: CAS No. 1337-76-4, purity 99%.

[0074] Sorbitan oleate: CAS No. 1338-43-8, purity 99%.

[0075] Octylphenol polyoxyethylene ether-10: Kaifeng Chentong Environmental Protection Technology Co., Ltd.

[0076] Cyclohexane: CAS No. 110-82-7, purity 99%.

[0077] Ammonia water: CAS No. 1336-21-6, purity 99%.

[0078] Ethyl orthosilicate: CAS No. 78-10-4, purity 99%.

[0079] Hexadecyltrimethoxysilane: CAS No. 16415-12-6, purity 99%. Specific embodiments

[0081] Preparation Example 1

[0082] This preparation example provides a hydrophobic ammonium polyphosphate-loaded nano-silica microcapsule, and the preparation method comprises the following steps: A1, mixing sorbitan oleate and octylphenol polyoxyethylene ether-10, adding cyclohexane and ammonia water, stirring and mixing evenly to obtain an oil phase;

[0083] A2, mixing ammonium polyphosphate and water in a weight ratio of 8:100, and dispersing and dissolving by ultrasonication to obtain an aqueous phase;

[0084] A3, under stirring, the water phase was added dropwise to the oil phase for 45 minutes, followed by emulsification for 30 minutes to form an oil-in-water emulsion, and finally ethyl orthosilicate was added dropwise for 45 minutes, followed by reaction for 24 hours to obtain an emulsion;

[0085] A4, the emulsion was demulsified with anhydrous ethanol, centrifuged three times, and then dried in an oven at 50° C. for 22 h to obtain non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules;

[0086] A5, mixing hexadecyltrimethoxysilane and anhydrous ethanol solution, and adding the non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules prepared in step A4, stirring at 60° C. for 5 h, and centrifuging and washing to obtain the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules;

[0087] In the step A1, the weight ratio of sorbitan oleate, octylphenol polyoxyethylene ether-10, cyclohexane and ammonia water is 8:1:90:3;

[0088] The weight ratio of the ammonium polyphosphate in step A2 to the sorbitan oleate in step A1 is 1.5:8;

[0089] In the step A3, the weight ratio of the tetraethyl orthosilicate to the sorbitan oleate is 30:8;

[0090] In the step A4, the weight ratio of the emulsion to the anhydrous ethanol is 2:1;

[0091] In the step A5, the weight ratio of the hexadecyltrimethoxysilane to the sorbitan oleate is 5:8;

[0092] In the step A5, the weight ratio of the hexadecyltrimethoxysilane to the anhydrous ethanol solution is 6:100.

[0093] Preparation Example 2

[0094] This preparation example provides a hydrophobic ammonium polyphosphate-loaded nano-silica microcapsule, and the preparation method comprises the following steps: A1, mixing sorbitan oleate and octylphenol polyoxyethylene ether-10, adding cyclohexane and ammonia water, stirring and mixing evenly to obtain an oil phase;

[0095] A2, mixing ammonium polyphosphate and water in a weight ratio of 9:100, and dispersing and dissolving by ultrasonication to obtain an aqueous phase;

[0096] A3, under stirring, the water phase was added dropwise to the oil phase for 55 minutes, followed by emulsification for 40 minutes to form a water-in-oil emulsion, and finally ethyl orthosilicate was added dropwise for 55 minutes, followed by reaction for 24 hours to obtain an emulsion;

[0097] A4, the emulsion was demulsified with anhydrous ethanol, centrifuged for 3 times, and then dried in an oven at 50° C. for 23 h to obtain non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules;

[0098] A5, mixing hexadecyltrimethoxysilane and anhydrous ethanol solution, and adding the non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules prepared in step A4, stirring at 65° C. for 5.5 h, and centrifuging and washing to obtain the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules;

[0099] In step A1, the weight ratio of sorbitan oleate, octylphenol polyoxyethylene ether-10, cyclohexane and ammonia water is 8:1:96:4;

[0100] The weight ratio of the ammonium polyphosphate in step A2 to the sorbitan oleate in step A1 is (1.5-2):8;

[0101] In step A3, the weight ratio of tetraethyl orthosilicate to sorbitan oleate is 30:9;

[0102] In step A4, the weight ratio of the emulsion to anhydrous ethanol is 2:1;

[0103] In step A5, the weight ratio of hexadecyltrimethoxysilane to sorbitan oleate is 5.5:8;

[0104] In step A5, the weight ratio of the hexadecyltrimethoxysilane to the anhydrous ethanol solution is 7:100.

[0105] Preparation Example 3

[0106] This preparation example provides a hydrophobic ammonium polyphosphate-loaded nano-silica microcapsule, and the preparation method comprises the following steps: A1, mixing sorbitan oleate and octylphenol polyoxyethylene ether-10, adding cyclohexane and ammonia water, stirring and mixing evenly to obtain an oil phase;

[0107] A2, mixing ammonium polyphosphate and water in a weight ratio of 10:100, and dispersing and dissolving by ultrasonication to obtain an aqueous phase;

[0108] A3, under stirring, the water phase was added dropwise to the oil phase for 60 minutes, followed by emulsification for 45 minutes to form a water-in-oil emulsion, and finally ethyl orthosilicate was added dropwise for 60 minutes, followed by reaction for 24 hours to obtain an emulsion;

[0109] A4, the emulsion was demulsified with anhydrous ethanol, centrifuged for 3 times, and then dried in an oven at 50° C. for 24 h to obtain non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules;

[0110] A5, mixing hexadecyltrimethoxysilane and anhydrous ethanol solution, and adding the non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules prepared in step A4, stirring at 70° C. for 6 hours, and centrifuging and washing to obtain the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules;

[0111] In step A1, the weight ratio of sorbitan oleate, octylphenol polyoxyethylene ether-10, cyclohexane and ammonia water is 8:1:100:5;

[0112] The weight ratio of the ammonium polyphosphate in step A2 to the sorbitan oleate in step A1 is 2:8;

[0113] In step A3, the weight ratio of tetraethyl orthosilicate to sorbitan oleate is 30:10;

[0114] In step A4, the weight ratio of the emulsion to the anhydrous ethanol is 2:1;

[0115] In step A5, the weight ratio of hexadecyltrimethoxysilane to sorbitan oleate is 6:8;

[0116] In step A5, the weight ratio of hexadecyltrimethoxysilane to the anhydrous ethanol solution is 8:100.

[0117] Example 1

[0118] This embodiment provides a water-based low-temperature paint, which includes the following raw materials in parts by weight:

[0119] 55 parts of water-based acrylic emulsion; 2 parts of amine neutralizer; 1 part of defoamer; 30 parts of titanium dioxide; 1 part of sodium dodecylbenzene sulfonate; 1 part of leveling agent; 4 parts of polypropylene glycol; 18 parts of deionized water; 6 parts of ethanol; 4 parts of diethylene glycol butyl ether; 5 parts of propylene glycol butyl ether; 1 part of thickener; 3 parts of light stabilizer; 5 parts of water-based silane coupling agent; 10 parts of hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate; 5 parts of attapulgite.

[0120] The defoaming agent in this embodiment is selected from silicone oil defoaming agents.

[0121] The leveling agent in this embodiment is selected from diacetone alcohol.

[0122] The thickener in this embodiment is selected from associative polyurethane thickeners.

[0123] The light stabilizer in this embodiment is selected from benzotriazole light stabilizer.

[0124] The preparation method of the water-based low-temperature paint in this embodiment comprises the following steps:

[0125] S1, mixing deionized water, sodium dodecylbenzene sulfonate, hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules, and attapulgite to prepare a first mixture;

[0126] S2, mixing diethylene glycol butyl ether, propylene glycol butyl ether and the first mixed material, and then adding titanium dioxide to obtain a second mixed material;

[0127] S3, adding the water-based acrylic emulsion and the amine neutralizer to the second mixture, and then adding the light stabilizer and the water-based silane coupling agent, mixing and stirring to obtain a third mixture;

[0128] S4. Add the remaining ingredients to the third mixture, stir and mix them evenly at a speed of 700 r / min for 8 minutes to obtain a water-based low-temperature paint.

[0129] Embodiment 2-4

[0130] Example 2

[0131] The difference between this embodiment and embodiment 1 is that when preparing water-based low-temperature paint, the total weight of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 24 parts, and the weight ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 1.8:1.

[0132] Example 3

[0133] The difference between this embodiment and embodiment 1 is that when preparing water-based low-temperature paint, the total weight of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 24 parts, and the weight ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 2.2:1.

[0134] Example 4

[0135] The difference between this embodiment and embodiment 1 is that when preparing water-based low-temperature paint, the total weight of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 24 parts, and the weight ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 2.3:1.

[0136] Comparative Examples 1-3

[0137] Comparative Example 1

[0138] The difference between this comparative example and Example 1 is that when preparing the water-based low-temperature paint, no hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate are added.

[0139] Comparative Example 2

[0140] The difference between this comparative example and Example 1 is that attapulgite is not added when preparing the water-based low-temperature paint.

[0141] Comparative Example 3

[0142] The difference between this comparative example and Example 1 is that, when preparing the water-based low-temperature paint, attapulgite and hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules are not added.

[0143] Experimental testing:

[0144] Waterproofness: Test the water resistance of the paint film in accordance with GB / T5209-1985 "Determination of water resistance of paints and varnishes" and record the time when bubbles, shedding, discoloration, etc. begin to appear.

[0145] Flame retardancy: GB / T2408-2021 standard test. The sample size is 80mm×10mm×1mm.

[0146] Adhesion: The adhesion grade of the paint film is tested in accordance with GB / T 9286-2021 "Paint and varnish, cross-cut test"; the water-based low-temperature paint of each embodiment and comparative example is applied on a wall with a size of 50mm*11200mm*(3-6)mm using a wet film preparation device, and the paint film thickness is 100μm. The wall is placed at 20±2℃ for 2 hours, and professionals observe the film formation. If the film is formed normally, the surface will be slightly sticky when touched by a finger, but there will be no paint sticking to the finger, and there will be basically no traces of the base material on the surface; otherwise, there will be obvious traces of the base material on the surface, and it will be white.

[0147] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.

[0148] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-3

[0149] Example Water resistance / d Flame retardant Adhesion Low temperature city model (20℃) Example 1 53 V-0 Level 1 Film forming, no trace on the surface Example 2 45 V-0 Level 1 Film forming, no trace on the surface Example 3 50 V-0 Level 1 Film forming, no trace on the surface Example 4 48 V-0 Level 1 Film forming, no trace on the surface Comparative Example 1 20 V-2 Level 2 Obvious traces can be observed on the surface Comparative Example 2 18 V-1 Level 2 Obvious traces can be observed on the surface Comparative Example 3 13 HB Level 3 Obvious traces can be observed on the surface

[0150] Analysis of results: The difference between Example 2-4 and Example 1 is that, when preparing water-based low-temperature paint, the weight ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is different. Combined with the experimental test results in Table 1, it can be seen that when the weight ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 2:1, the obtained water-based low-temperature paint has better compressive strength, crack resistance and water permeability.

[0151] The difference between Comparative Example 1 and Example 1 is that when preparing water-based low-temperature paint, no hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate are added. The difference between Comparative Example 2 and Example 1 is that no attapulgite is added when preparing water-based low-temperature paint. The difference between Comparative Example 3 and Example 1 is that when preparing water-based low-temperature paint, no attapulgite and hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate are added. Combining the experimental test results of Example 1 and Comparative Examples 1-3, it can be seen that when preparing water-based low-temperature paint, when attapulgite and hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate are compounded and used, the flame retardancy, adhesion and waterproof performance of the water-based low-temperature paint obtained can be improved. The reason may be that the hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate and attapulgite work together in water-based low-temperature paint. Due to its special structural design, the hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate can be evenly dispersed in the coating and used as flame retardant storage units. When the coating is heated, the ammonium polyphosphate in the microcapsules can be quickly released, which has an effective flame retardant effect. The hydrophobicity of the nano-silica itself is conducive to improving the water resistance of the coating. As a functional filler, attapulgite not only enhances the density of the coating, thereby improving the waterproof performance, but also its special layered structure and physical adsorption may help improve the bonding strength between the coating and the substrate and enhance the adhesion.

[0152] Examples 2-4 tested different ratios of the two components and verified that at a specific weight ratio (e.g., 2:1), the best comprehensive performance, including compressive strength, crack resistance, and water permeability, can be obtained. In the comparative experiment, Comparative Example 1 lacked only the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules, showing a decrease in flame retardancy and water resistance; Comparative Example 2 lacked attapulgite, affecting water resistance and adhesion; Comparative Example 3 lacked both, and all aspects of performance were inferior to Example 1. These comparative results clearly show that the composite application of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite in water-based low-temperature paints is crucial to improving overall performance.

[0153] Embodiment 5-6

[0154] Example 5

[0155] The difference between this embodiment and embodiment 1 is that, when preparing the water-based low-temperature paint, the weight percentages of some components are changed. The differences are shown in Table 2.

[0156] Table 2 - Differences between Example 5-6 and Example 3

[0157] Ingredients (portions) Example 1 Example 5 Example 6 Water-based acrylic emulsion 55 65 75 Amine Neutralizer 2 3 4 Defoaming agent 1 2 3 Titanium dioxide 30 33 35 Sodium dodecylbenzenesulfonate 1 1.8 2 Leveling agent 1 1.2 1.5 Polypropylene glycol 4 5 6 Deionized water 18 22 25 Ethanol 6 7 9 Diethylene glycol butyl ether 4 8 10 Propylene glycol butyl ether 5 7 8 Thickener 1 2 3 Light Stabilizer 3 4 5 Water-based silane coupling agent 5 7 9 Hydrophobic ammonium polyphosphate loaded nano-silica microcapsules 16 16 16 Attapulgite 8 8 8

[0158] The experimental test results of Examples 5-6 are shown in Table 3.

[0159] Table 3 - Experimental test results of Examples 5-6

[0160] Example Water resistance / d Flame retardant Adhesion Low temperature city model (20℃) Example 1 53 V-0 Level 1 Film forming, no trace on the surface Example 5 59 V-0 Level 1 Film forming, no trace on the surface Example 6 56 V-0 Level 1 Film forming, no trace on the surface

[0161] Result analysis: Combined with the experimental test results in Table 3, it can be seen that when preparing water-based low-temperature paint, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that the comprehensive performance of the water-based low-temperature paint prepared in Example 5 is better.

[0162] Embodiment 7-11

[0163] Example 7

[0164] The difference between Examples 7-11 and Example 5 is that when preparing water-based low-temperature paint, on the premise that the weight ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 2:1, the total weight ratio of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite in the water-based low-temperature paint is changed, and the optimal weight ratio is selected.

[0165] In Example 5, the total weight of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and attapulgite is 24 parts, and the total weight of the water-based low-temperature paint is 192 parts.

[0166] Therefore, it is not difficult to conclude that in Example 5, the proportion of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules (called variable 1) and attapulgite (called variable 2) in the water-based low-temperature paint (called the matrix) is 12.5%.

[0167] The differences between Examples 7-11 and Example 5 are shown in Table 4.

[0168] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.

[0169] Table 4 - Differences between Examples 7-11 and Example 5

[0170]

[0171] The experimental test results of Examples 7-11 are shown in Table 5.

[0172] Table 5 - Experimental test results of Examples 7-11

[0173]

[0174]

[0175] Results analysis: Combined with the experimental test results in Table 5, it can be seen that when preparing water-based low-temperature paint, when the total weight of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules (called variable 1) and attapulgite (called variable 2) in the water-based low-temperature paint is 12.50-15.15%, the comprehensive performance of the water-based low-temperature paint is better. When the total weight of hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules (called variable 1) and attapulgite (called variable 2) in the water-based low-temperature paint is 14.50%, the comprehensive performance of the water-based low-temperature paint is the best.

[0176] Examples 12-13

[0177] Example 12

[0178] The difference between this embodiment and embodiment 10 is that, when preparing water-based low-temperature paint, the preparation parameters of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules used are different. The hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules in this embodiment are prepared by Preparation Example 2.

[0179] Embodiment 13

[0180] The difference between this embodiment and embodiment 10 is that, when preparing water-based low-temperature paint, different preparation parameters are used for the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules. The hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules in this embodiment are prepared by Preparation Example 3.

[0181] The experimental test results of Examples 12-13 are shown in Table 6.

[0182] Table 6 - Experimental test results of Examples 12-13

[0183] Example Water resistance / d Flame retardant Adhesion Low temperature city model (20℃) Example 10 71 V-0 Level 0 Film forming, no trace on the surface Example 12 78 V-0 Level 0 Film forming, no trace on the surface Embodiment 13 75 V-0 Level 0 Film forming, no trace on the surface

[0184] Result analysis: The difference between Examples 12-13 and Example 10 is that when preparing water-based low-temperature paint, the preparation methods of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules used are different. Combined with the experimental test results in Table 6, it can be seen that the comprehensive performance of the water-based low-temperature paint prepared by Example 1 is better.

[0185] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A water-based low-temperature paint, characterized in that: The water-based low-temperature paint comprises the following raw materials by weight: 5575 parts of water-based acrylic emulsion; 24 parts of amine neutralizer; 13 parts of defoaming agent; 30-35 parts of titanium dioxide; Sodium dodecylbenzenesulfonate 12 parts; 11.5 parts of leveling agent; 46 parts of polypropylene glycol; 1825 parts of deionized water; Ethanol 69 parts; 410 parts of diethylene glycol butyl ether; Propylene glycol butyl ether 58 parts; Thickener 13 parts; 35 parts of light stabilizer; 5-9 parts of water-based silane coupling agent; 10-20 parts of hydrophobic nano-silica microcapsules loaded with ammonium polyphosphate; 5-10 parts of attapulgite; The preparation method of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules is as follows: A1, sorbitan oleate and octylphenol polyoxyethylene ether-10 were mixed, and cyclohexane and ammonia water were added, and the mixture was stirred to obtain an oil phase; A2, mixing ammonium polyphosphate and water in a weight ratio of (8-10):100, dispersing and dissolving by ultrasonication to obtain an aqueous phase; A3, under stirring, the water phase is added dropwise to the oil phase for 45-60 minutes, followed by emulsification for 30-45 minutes to form a water-in-oil emulsion, and finally, ethyl orthosilicate is added dropwise for 45-60 minutes, followed by reaction for 24 hours to obtain an emulsion; A4, the emulsion was demulsified with anhydrous ethanol, centrifuged for 3 times, and then dried in an oven at 50°C for 22-24 h to obtain non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules; A5, mixing hexadecyltrimethoxysilane and anhydrous ethanol solution, and adding the non-hydrophobically modified ammonium polyphosphate-loaded nano-silica microcapsules obtained in step A4, stirring at 60-70° C. for 5-6 hours, and centrifuging and washing to obtain the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules; In the step A1, the weight ratio of sorbitan oleate, octylphenol polyoxyethylene ether-10, cyclohexane and ammonia water is 8:1:(90-100):(3-5); The weight ratio of the ammonium polyphosphate in step A2 to the sorbitan oleate in step A1 is (1.5-2):8; In the step A3, the weight ratio of the tetraethyl orthosilicate to the sorbitan oleate is 30:(8-10); In the step A4, the weight ratio of the emulsion to the anhydrous ethanol is 2:1; In the step A5, the weight ratio of the hexadecyltrimethoxysilane to the sorbitan oleate is (5-6):8; In the step A5, the weight ratio of the hexadecyltrimethoxysilane to the anhydrous ethanol solution is (6-8):

100.

2. The water-based low-temperature paint according to claim 1, characterized in that: The weight ratio of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules to the attapulgite is (1.8-2.3):

1.

3. The water-based low-temperature paint according to claim 1, characterized in that: The weight ratio of the nano-silicon dioxide microcapsules loaded with ammonium polyphosphate to the attapulgite is 2.0:

1.

4. The water-based low-temperature paint according to claim 1, characterized in that: The total weight of the hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules and the attapulgite accounts for 12.50-15.15% of the total weight of the water-based low-temperature paint.

5. The water-based low-temperature paint according to claim 1, characterized in that: The defoaming agent is selected from silicone oil defoaming agents.

6. The water-based low-temperature paint according to claim 1, characterized in that: The leveling agent is selected from diacetone alcohol.

7. The water-based low-temperature paint according to claim 1, characterized in that: The thickener is selected from associative polyurethane thickeners.

8. The water-based low-temperature paint according to claim 1, characterized in that: The light stabilizer is selected from benzotriazole light stabilizers.

9. A method for preparing the water-based low-temperature paint according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1, mixing deionized water, sodium dodecylbenzene sulfonate, hydrophobic ammonium polyphosphate-loaded nano-silica microcapsules, and attapulgite to prepare a first mixture; S2, mixing diethylene glycol butyl ether, propylene glycol butyl ether and the first mixed material, and then adding titanium dioxide to obtain a second mixed material; S3, adding the water-based acrylic emulsion and the amine neutralizer to the second mixture, and then adding the light stabilizer and the water-based silane coupling agent, mixing and stirring to obtain a third mixture; S4. Add the remaining ingredients to the third mixture, stir and mix them evenly at a speed of 600-800 r / min for 5-10 minutes to obtain the water-based low-temperature paint.